Multiple Simultaneous Gastrointestinal Parasitic Infections in a Patient with Human Immunodeficiency Virus - Del Pilar-Morales, Esteban A.; Cardona-Rodríguez, Zaydalee; Bertrán-Pasarell, Jorge; Soto-Malave, Ruth; De León-Borras, Rafeal (Puerto Rico Health Sciences Journal, 2016)
Patients with the human immunodeficiency virus (HIV) infection are at high risk for gastrointestinal infections causing diarrhea, particularly when those infections are parasitic in nature. This propensity is more pronounced in AIDS, where opportunistic parasitic infections may cause severe diarrhea, marked absorptive dysfunction, and significant risk of mortality. There are scant data regarding parasitic infections among HIV patients in the developed world; most studies and research come from povertystricken areas of South Africa, India, Iran, and the South Pacific. Although multiple infections with the same or different parasites have been reported, simultaneous infections are rare. We present the case of a 35-year-old man who developed a co-infection with Giardia, Cryptosporidium, and Strongyloides, simultaneously, the diagnosis being made after the judicious evaluation of a stool sample. Given the associated morbidity, prompt diagnosis and treatment are needed to avoid further complications in patients with HIV. To our knowledge this is the first reported case of triple parasitic infection in a patient with HIV.